Lessons from the Reconstruction of Post-Tsunami Aceh : Build Back Better Through Ensuring Women are at the Center of Reconstruction of Land and Property - Bell, Keith Clifford (World Bank, Washington, DC, 2012)
On December 26 2004, a 9.3 magnitude earthquake struck the Indian Ocean and unleashed a blast of energy, creating a tsunami three stories high. The disaster which claimed more than 228,000 lives had an impact on the lives of more than 2.5 million people causing close to US$ 11.4 billion of damage in 14 countries. The highest price was paid in Aceh, which had the greatest death toll of 130,000 confirmed dead and a further 37,000 reported missing. In Banda Aceh, the capital of the province, the tsunami claimed more than one-third of the city's population. An estimated 500,000 people were displaced by the disaster and some 250,000 houses damaged or destroyed. More than 500 miles of coastline was affected, with an estimated 53,795 parcels of land permanently destroyed through erosion or submersion. Documentation of land ownership was largely destroyed and physical evidence, such as walls, fences and boundary markers were completely eradicated. The tsunami and earthquake not only shattered housing and other coastal infrastructure, but it also shook the very foundations of the Acehnese society and the social capital that had taken decades to build up, in the midst of a thirty year civil war. As is usually the case during times of disaster and emergency, women bore the greatest burden as the tsunami deprived them of the existing safety nets offered by their families, especially spouses or parents. This smart lesson describes the experience of the World Bank's emergency response team who worked to support the reconstruction of post-tsunami Aceh and North Sumatra and how this served as important entry point to address women's land and property rights.